Pengaruh Penerapan Sistem Blok dan Metode Resitasi terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam - Imron Muslimin; Yasmaruddin Bardansyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to see whether there is a significant effect of the implementation of block system and recitation method on students’ learning outcome of Islamic Education subject at SMK Negeri Pertanian Terpadu, Riau Province. The population of this study was all Muslim students of class XII PAI of SMK Negeri Pertanian Terpadu Riau Province with a total of 429. The sample in this study was determined by probability sampling technique, namely simple random sampling by using Slovin formula with an error rate of 5%, so that the number of samples in this study were 207 students. The data were collected by using questionnaire and analyzed by using multiple linear regression analysis. The results of the analysis showed that the t value for the implementation of block system variable (X1) was 2,898 and the value of the implementation of recitation method variable (X2) was 2.939. Meanwhile the t table value for n = 207 with degrees of freedom nk-1 = 204 and level 5% confidence was 2.258. Therefore, it can be concluded that the implementation of block system and recitation method variables partially affected the learning outcomes of students. The f value for the implementation of block system and recitation method variable was 26.126, which was greater than the f table value of 3.040. Thus, it can be concluded that there was a significant effect of the implementation of block system and recitation method on students’ learning outcomes jointly. Meanwhile, based on the R2 test, it was known that the coefficient of determination (R2) was 0.204. It means that the contribution of the implementation of block system and recitation method was 20.4%. Meanwhile, 79.6% was influenced by other variables which were not included in this study.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//